Relationship of some physical traits and motor balance By performing the scoring from the jump when the basketball players Descriptive research (Journal of the College of Basic Education, 2022)
In order to reach the high level of sports for each athlete in various sports events, he mustHe goes through several aspects of preparation, including what is physical, skillful, tactical and psychological, and these are the foundations of training.In the game of basketball, the performance of the players when they are shooting from the state of jumping is distinguished by a number ofThe factors, including those related to the psychological, technical, mechanical and physical aspects, which increase the effectiveness of And the strength of competitive performance during matches.